Avaliação da qualidade da água subterrânea utilizada para consumo humano na região rural do município de Toledo-PR - Pauli, Aline Roberta de (2014)
Freshwater is a naturally scarce resource because there are few sources of that water-type around the world. Moreover, pollution and uncontrolled use of water resources are increasing this shortage. In particular, groundwater is a major source of freshwater for human use in the city of Toledo PR, where the quality of groundwater is often not assessed and checked for its potability recommended standards. This study aims to monitor and assess the quality of groundwater used for human consumption in the rural municipality of Toledo - PR. Groundwaters of ten deep wells were monthly sampled during a year (November/2012 to October/2013) in this regard. Elemental content measurements were performed by using the both highly-sensitivity techniques of Total reflection X-ray Fluorescence (TXRF) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The mean values of physico-chemical parameters and elemental content of the groundwater were statistical correlated and compared with the current Brazilian environmental legislation. A cluster analysis was made as well in order to assess the similarity of the water composition among the set of the sampled groundwaters of studied wells. In addition, a canonical correspondence analysis was also applied to assess the possible relationship based on the characteristics of wells, such as depth, age of the plumbing and distance from the septic tank and water quality. A water balance was performed, verifying surplus and water deficiency at the study site. According to the results, all the assessed wells showed some disagreement regarding the maximum allowable values for the parameters analyzed by Ordinance No. 2914 of the Ministry of Health (BRAZIL, 2011) for drinking water, requiring this water to be treated so that it can be consumed without risk to health. Using a cluster analysis, it was found that some of the closest wells were also geographically more similar in their chemical composition and it is likely that the chemical characteristics of the well waters are related to the rock in which the aquifer is inserted. The canonical correspondence analysis showed little influence on the characteristics of well water quality. Using a water balance, it was observed that there is surplus water in almost all months studied, indicating that there may be aquifer recharge, which influences the quality of groundwater.